Efficacy and safety of selamectin of flea infestation in dags - SOTIRAKI (Σ. ΣΩΤΗΡΑΚΗ) S.; HIMONAS (Χ. ΧΕΙΜΩΝΑΣ) C.; DEBOUCK, P.; BITSAS (Γ. ΜΠΙΤΖΑΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The study was conducted at three dog shekers in Thessaloniki Greece, το confirm die efficacy and safety of selamectin aτ a minimum dosage of 6 mg/kg adminisτered topically as a monthly dose repeaτed three times in die treatment of natural i n f l a t i o n s of Ctenocephalides spp. Twenty (20) dogs, with confirmed naturally acquired flea inflations, were enrolled in die sttidy as primary patiems. All animals completed the study on day 90. Twenty-two in cornai dogs were also treated but not evaluated for efficacy (secondary patiems). There was no untreated group. Only one live adult flea was recovered on only one animal on study day 30, a reduction of die geomettical mean of 99.7 % (p < 0.0001) compared to the sτarτ of die study. Dead fleas were found on 3 animals aτ day 30 (1 or 2 per animal). No live or dead fleas were found on day 60 or on day 90. Ατ sttidy beginning on Day 0, seventy percem of sttidy animals had various clinical signs of flea inflation. These signs gradually decreased and by die end of die sttidy on day 90, only one animal remained widi a score of 1, indicating a low imensity in a single area of die body. All odier animals were free of clinical signs. No abnormal clinical signs or suspend adverse drug reactions were observed after treatment of die 20 primary or die 22 secondary patiems. The daτa collected confirm that under field conditions diree consecutive mondily doses of selamectin are highly effective and safe in die treatment and comrol of fleas in dogs.